2014
DOI: 10.4103/0300-1652.144693
|View full text |Cite
|
Sign up to set email alerts
|

Motorcycle-related injuries at a university teaching hospital in north central Nigeria

Abstract: Background:Motorcycle-related injuries lead to considerable morbidity and mortality. The aim of this study is to determine the pattern and outcome of motorcycle-related injuries at Benue State University Teaching Hospital, Makurdi, Nigeria.Patients and Methods:Case records of all patients who presented to the accident and emergency department with motorcycle-related injuries between July 2012 and June 2013 were analysed for age, gender, injury host status (i.e. rider, pillion or pedestrian), nature of collisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
5
4
0
Order By: Relevance
“…It has been reported to account for 7.2% of gunshots in North-Central Nigeria. [ 9 ] We found a male preponderance, most of whom are in the third and fourth decades of life consistent with other findings within and outside Nigeria. [ 7 9 10 ] This depicts the potential catastrophic sequel of these injuries as patients are in the productive age group with far-reaching consequences to their families and the nation at large.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported to account for 7.2% of gunshots in North-Central Nigeria. [ 9 ] We found a male preponderance, most of whom are in the third and fourth decades of life consistent with other findings within and outside Nigeria. [ 7 9 10 ] This depicts the potential catastrophic sequel of these injuries as patients are in the productive age group with far-reaching consequences to their families and the nation at large.…”
Section: Discussionsupporting
confidence: 90%
“…According to a study done in Nigeria, 70% of the riders were less than 40 years of age. [18] Similar percentages were observed in this study too. However, 28% of the pillion riders in this study were less than 20 years.…”
Section: Figure 07 -Category Of Hurt Of the Motor Cycle Occupants Dissupporting
confidence: 89%
“…[7,9,12 ] Lower ratios were observed in studies done in Cameroon (1.09:1) Nigeria (3.9:1), and Tanzania (2.3:1). [17,18,10] In a study done in Karachi, the observed ratio was 5.7:1, which is much similar to the overall ratio observed in this study. Even though the ratios are high for motorcycle riders in our country, it is very low for the pillion riders.…”
Section: Figure 07 -Category Of Hurt Of the Motor Cycle Occupants Dissupporting
confidence: 89%
See 1 more Smart Citation
“…described the pattern and outcome of motorcycle-related injuries at a university hospital in Makurdi, Nigeria. 1 In Iran, we had conducted a hospital-based study to evaluate the fatal injuries associated with motor vehicle crashes, and we obtained a burdensome rate of 20% mortality rate among motor vehicle crashes. 2 Iran, a country that has challengeable problems related to this vital issue of public health, suffers a substantial economic loss each year due to fatal injuries because of a variety of reasons.…”
mentioning
confidence: 99%